Analysis of the Development of MOOCs Assisted Digital Teaching Materials on Impulsive and Momentum Materials to Train Critical Thinking Skills in Bengkulu City High Schools - Sheila Selvyana Widodo (CV. Media Inti Teknologi, 2022)
Investigating the feasibility of the product and students' response to it is the main goal of this R&D. The 4-D development paradigm used in this study consists of the following stages: defining, designing, developing, and dissemination stages. In this study, students from secondary schools in Bengkulu City, SMAN 02, SMAN 4 and SMAN 09 took part. The focus of this research is to train students' critical thinking skills through participation in massive open online courses (MOOCs) with topics related to assisted impulses and momentum. Eighty-eight students from three institutions were surveyed, and their answers were validated by two professional lecturers and three physics professors. Classroom observations, interviews with instructors and students, questionnaires tailored to their needs, expert validation, and analysis of quantitative and qualitative responses provided data for research. The average percentage of respondents who strongly agreed with the statement that teachers' needs were met was 89.68 percent; Respondents who agreed with the statement of student needs were 73.92 percent.